Characteristics and control modes of geothermal fields in deep coal reservoirs in the Linxing-Shenfu block - Lifu XU; Yuhu BAI; Bingxiang XU; Weiqiang HU; Jianqi CHEN; Yong LI (Meitian dizhi yu kantan)
ObjectiveGeothermal fields serve as a crucial geological condition controlling the phases and seepage of deep coalbed methane (CBM). Investigating geothermal fields facilitates the assessment and efficient development of deep CBM resources.MethodsThis study explored the Nos. 8 and 9 coal seams in the Linxing-Shenfu block using data from drilling, well logging, well tests, and experiments. Specifically, this study summarized the regional distribution patterns of geothermal fields in deep coal reservoirs in the block, analyzed the impacts of the geothermal fields on the gas-bearing and physical properties of the reservoirs, and revealed the controlling factors and mechanisms of the geothermal fields. Furthermore, it proposed differential control modes of regional geothermal fields in the block.Results and ConclusionsThe results indicate that coal seams in the study area have a present-day average temperature of about 52 ℃ and geothermal gradients ranging from 1.72 ℃/hm to 2.64 ℃/hm (average: 2.21 ℃/hm), suggesting slightly low to normal geothermal gradients. The geothermal fields in the study area are negatively correlated with the adsorption capacity and mechanical properties of coal seams but are weakly positively correlated with their permeability. Specifically, higher geothermal gradients and reservoir temperatures correspond to lower critical depths of gas content in coal seams, a higher amount of adsorbed gas converted to free gas, and improved reservoir permeability. In contrast, higher geothermal gradients are associated with lower peak strength, smaller modulus of elasticity, and enhanced plasticity of coals. The geothermal fields in the study area are influenced by multiple factors, including burial depth, structures, groundwater, and the thermal conductivity of rocks. The small differences in the lateral thermal conductivity of strata result in the lateral heat transfer, followed by heat accumulation in uplift zones. As a result, high-temperature geothermal fields are formed. In contrast, faults destroy strata or connect groundwater, leading to thermal diffusion. Consequently, lower-temperature geothermal fields are formed. Four temperature control modes of geothermal fields in the study area are identified: (1) The universal mode with temperature controlled by horizontal strata, characterized by normal geothermal gradients but reservoir temperatures varying with the burial depth. (2) The mode with temperature primarily governed by lateral heat transfer, occurring in Zijinshan basement uplift. (3) The mode with temperature primarily influenced by faults, observed in the northern Linxing and western Shenfu blocks. (4) The composite mode with temperature dominated by both faults and groundwater, occurring in the eastern Shenfu block. This study reveals the distribution patterns of geothermal fields in the study area and their impacts on the physical properties of deep coal reservoirs. Under similar geological conditions, structurally higher parts with high-temperature geothermal fields are more enriched in free gas. Therefore, it is recommended that these parts serve as significant zones for resource assessment to promote the high production of deep CBM.